Phytochemical analysis and antibacterial activity of Andrographis lineata Nees (Acanthaceae) - Kumari, B. K. Rathna; Raveesha, H. R. (Current Botany, 2024)
Andrographis lineata Nees is an erect herb and has been used as a traditional medicine against many diseases. The present study was to investigate the phytochemical analysis and antibacterial activity of A. lineata plant extracts. The methanolic extracts of A. lineata showed a variety of phytochemicals such as alkaloids, flavonoids, phenols, tannins, terpenoids etc. The quantitative estimation of major phytochemical constituents revealed maximum amount of phenolic content in the roots and alkaloids in both the stem and leaf. Correspondingly, the highest amount of tannins and terpenoids were recorded in the leaf and flavonoids in the root samples. Furthermore, the plant extracts of A. lineata showed antibacterial activity against both Gram-positive and Gram-negative bacterial strains. Comparatively, stem extract was effective against Streptococcus mutans (18.19±0.04 mm), leaf extract against Enterobacter faecalis (24.13±0.14 mm) and root extract against Bacillus subtilis (24.09±0.14 mm) at 30 μg/μL concentration. However, the leaf extract was more effective against Escherichia coli (25.13±0.16 mm), Pseudomonas aeruginosa (20.20±0.13 mm) and Klebsiella pneumoniae (18.18±0.17 mm) at 30 μg/μL concentration. The studies infer that the phytochemical constituents of A. lineata have antibacterial properties and these herbs may be considered as the medicinal plant for treating bacterial diseases.